2010
DOI: 10.1089/ars.2009.2957
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species-Dependent c-Fos/Activator Protein 1 Induction Upregulates Heme Oxygenase-1 Expression by Bradykinin in Brain Astrocytes

Abstract: Heme oxygenase-1 (HO-1) plays a crucial role in tissue pathological changes such as brain injuries. Our previous studies have demonstrated that bradykinin (BK) induces the expression of several inflammatory proteins, including matrix metalloproteinase-9 and COX-2, via mitogen-activated protein kinases and nuclear factor-κB (NF-κB) in rat brain astrocytes (RBA-1). However, the molecular mechanisms underlying BK-induced HO-1 expression in RBA-1 cells remain poorly defined. Here we demonstrated that BK induced HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 54 publications
11
38
0
Order By: Relevance
“…Because EC treatment reduced HO-1 protein expression, we speculate that EC might activate an Nrf2-independent pathway that modulates HO-1 expression and iron deposition in the CCI model. This finding is in line with previous studies which showed that activator protein 1 (AP-1) regulates HO-1 gene expression in Nrf2-deficient fibroblasts [56] and normal brain astrocytes [57]. AP-1 is a stress-activated transcription factor and has been regarded as an inflammatory signaling molecule after TBI [58].…”
Section: Discussionsupporting
confidence: 91%
“…Because EC treatment reduced HO-1 protein expression, we speculate that EC might activate an Nrf2-independent pathway that modulates HO-1 expression and iron deposition in the CCI model. This finding is in line with previous studies which showed that activator protein 1 (AP-1) regulates HO-1 gene expression in Nrf2-deficient fibroblasts [56] and normal brain astrocytes [57]. AP-1 is a stress-activated transcription factor and has been regarded as an inflammatory signaling molecule after TBI [58].…”
Section: Discussionsupporting
confidence: 91%
“…Although NF-jB has been shown to be induced by stimuli that also up-regulate HO-1, its role in HO-1 gene expression is unclear in the literature. More than one study suggests a direct relationship between NF-jB activation and HO-1 induction (Hsieh et al 2010;Juan et al 2005); however, others show HO-1 expression is negatively controlled by NF-jB activity (Hartsfield et al 1998;Rushworth et al 2010). Our data demonstrate that NF-jB appears to be directly involved in HO-1 gene expression in response to arsenic in SVEC4-10 cells, because treatment of cells with Bay11-7082 (IjB-a phosphorylation inhibitor) significantly attenuates the induction.…”
Section: Discussionmentioning
confidence: 54%
“…Mechanistically, NOX activation is associated with increased intracellular Ca 2+ [46,47], protein kinase C (PKC) functions [81-83] and participates in the cell signaling processes. NOX derived O 2 .− contributes to the expression of matrix metalloproteinase-9 (MMP-9) and the activation of extracellular signal-regulated kinase (ERK) [81,82], c-Jun-N-terminal kinase (JNK) and nuclear factor kappa-B (NF-kB) [82-84]. Consequently, NOX up-regulation has been implicated in microglia activation/proliferation [21,63,85], inflammation [39,40,86,87] and mediated apoptotic neuronal death [44,45,88].…”
Section: Discussionmentioning
confidence: 99%